Os jornalistas do "Estado de Minas" e o uso da internet como fonte de pesquisa - Evaldo Fonseca Magalhaes (2005)
This dissertation is a study of users of information and deals with the use of internet during work activities by journalists of the newspaper Estado de Minas, from Belo Horizonte. The case study was conducted between august2004 and january2005. It questions how the users adopt the World Wide Web and its tools to obtain information that alows them to formulate themes to daily covering, contextualize and deepen the subjects that will become news. Moreover it analyses credibility and confiability of information gathered with internet tools, according to the journalists, and verify whether they check or not, by others means, the material obtained this way. It also describes the recent world productive reestruturation, the effects of the implantation of new information technologies, the organizational environment in the newsroom and the presence of journalists in this context. The results indicate that the internet, although being considered very important as a research system in a newsroom, still causes concern among professionals, regarding the quality of information found. Time pressure is as important factor in the production process of the news and, in many cases, causes this concern to be desconsidered.